2006
DOI: 10.1542/peds.2006-0092
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cerebral Blood Flow Velocity in Children With Mild Sleep-Disordered Breathing: A Possible Association With Abnormal Neuropsychological Function

Abstract: Objective-Sleep-disordered breathing describes a spectrum of upper airway obstruction in sleep from simple primary snoring, estimated to affect 10% of preschool children, to the syndrome of obstructive sleep apnea. Emerging evidence has challenged previous assumptions that primary snoring is benign. A recent report identified reduced attention and higher levels of social problems and anxiety/depressive symptoms in snoring children compared with controls. Uncertainty persists regarding clinical thresholds for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 58 publications
6
68
1
1
Order By: Relevance
“…An interesting association between executive dysfunction and SDB can be inferred from studies on cerebral blood flow in children with SDB e a study by Hill et al [152] found that in healthy children with mild SDB (AHI < 5/hTST), increased cerebral blood flow velocities were strongly correlated with decreased executive function as compared to healthy controls. The marked overlap between the presence of endothelial dysfunction and cognitive deficits in children with SDB is not only striking but further suggests that altered endothelial function may adversely affect the survival of neurons in highly susceptible regions such as the frontal cortex [153,154].…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…An interesting association between executive dysfunction and SDB can be inferred from studies on cerebral blood flow in children with SDB e a study by Hill et al [152] found that in healthy children with mild SDB (AHI < 5/hTST), increased cerebral blood flow velocities were strongly correlated with decreased executive function as compared to healthy controls. The marked overlap between the presence of endothelial dysfunction and cognitive deficits in children with SDB is not only striking but further suggests that altered endothelial function may adversely affect the survival of neurons in highly susceptible regions such as the frontal cortex [153,154].…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…(1) SDB has been linked to hypertension,(2) growth failure,(3) enuresis, (4,5) and impairment of cognition, attention, and executive functions. (6)(7)(8)(9)(10)(11)(12) Identification of children at high risk for SDB and its associated morbidities is particularly important given the growing body of evidence that treatment with adenotonsillectomy may improve quality of life and neurocognitive function. (5,(13)(14)(15)(16)(17) Preterm infants are especially vulnerable both to SDB and its sequelae.…”
mentioning
confidence: 99%
“…Whereas children with primary snoring have only a limited number of obstructive airway events during sleep, those with OSA characteristically experience varying, but more frequent episodes of airway obstruction. Although cognitive deficits have been described in children with SDB, evidence of a causal relationship between SDB and these deficits has not been firmly established (3)(4)(5)(6)(7)(8)(9). The absence of a dose-dependent association of cognitive deficits with increasing severity of OSA, coupled with findings of cognitive deficits in children with primary snoring, has challenged the notion of an adverse effect of SDB on cognition (10,11).…”
mentioning
confidence: 99%